The Leadership of Kiai Langgar as Head of Madrasah in Forming Students' Religious Character - Mohammad Zakki; Akhyak Akhyak; Ahmad Tanzeh; Binti Maunah; Imam Junaris (International Journal of Islamic Thought and Humanities, 2024)
Religious character education is a central government theme which aims to give birth to a generation of people who uphold values ​​in all aspects of life, so ideas and an active leadership role are needed from managers of Islamic educational institutions. The aim of this research is to determine the success of kiai as heads of madrasas and religious educators in the community in instilling character education. This research was implemented at Madrasah Ibtidaiyah (MI) Thufatut Tuhllab and MI Al Falah in Pamekasan District uses a descriptive qualitative approach. Data collection techniques were applied by means of observation, interviews and documentation and supported by analysis of the Milles and Hubermen models. The results of this research are that the motivation of a madrasa head in instilling character in students is based on the character of social concern, the spirit of fighting for weak students/society, istiqomah in carrying out sunnah worship, likes reading and practicing the Al-Qur’an. The leadership model developed to instill character values ​​includes democratic, transparent and transformative leadership and always provides motivation to members of the organization.